PENGARUH BERPIKIR KRITIS TERHADAP KREATIVITAS SISWA - Erinda Amalia Akmal; Nurlinda Safitri; Yudhie Suchyadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is quantitative research with a causal approach. This research aims to determine the influence of critical thinking on the creativity of class IV students at Cibening 01 State Elementary School, Pamijahan District, Bogor Regency. This research was conducted in the even semester of the 2022/2023 academic year. The population of this study was 64 students with a sample size of 39 students. Homogenous was used to test the hypothesis, the results of which showed that the influence of critical thinking on student creativity with statistical analysis produced a correlation coefficient (rxy) of 0.579. This shows the influence of critical thinking on student creativity, while the coefficient of determination (r2) is 0.336. or 33.6%, the remaining 66.4% is determined by other factors. The average creativity in students is 33.6% determined by critical thinking through the regression equation Ŷ= 34.56 + 0.733, meaning that every unit increase in critical thinking value will cause an increase in student creativity by 0.733 units. The calculation of the significance of the coefficient produces a tcount of 4,300 which is greater than a ttable of 2,100 with a real level which means it is significant. Based on the results of this research, it can be concluded that there is a positive influence between critical thinking on the creativity of class IV students at Cibening 01 State Elementary School, Pamijahan District, Bogor Regency, Even Semester, Academic Year 2022/2023. Keywords: Critical Thinking and Student Creativity.